Letter - Palmer, R. A.
030-0130-001 Telegraphic Address: "Congress Manchester" Telephone : Blackfriars 0975 (3 lines) Co-operative Union Ltd Head Office Holyoak House Hanover St MANCHESTER 4 Department Agriculture Education Finance Labour Legal Propaganda Publications Statistical GENERAL SECRETARY R.A. PALMER CONSULTING SOLICITORS W.A.S. SAN GARDE LLD, MANCHESTER D. B. MURRAY, GLASGOW DATE 29th June, 1938. RS/ML H.V. Tewson, Esq., The Assistant Secretary, Trades Union Congress, Transport House, Smith Square, London. S.W.1. Dear Mr. Tewson, I have today received an invoice from the C.W.S. for 210. 0. 0., covering the cost of soap supplied at your request to Spain. No doubt you will let me have a remittance in due course. Yours sincerely, R.A. Palmer Enclosure. 292/946/30/130